Tinjauan Aksiologi Terhadap Aliran Psikologi Behaviorisme - Irpan Zuhri; Sumaryati Sumaryati (Undiksha, 2022)
Analysis of behaviorism theory when viewed with axiology will reflect the field of philosophy with psychology. In addition, it also reflects the values and implementation of behaviorism in order to have a positive and useful impact on human life. The purpose of this study was to determine the axiological values that exist in the psychology of behaviorism, including ethics and aesthetics. The existence of a study of the axiological flow of behaviorism will certainly have a positive impact on knowledge of the value of the axiological flow or behaviorism approach so that its usefulness and application can be known in everyday life. This study uses a qualitative research method of literature study with content analysis techniques, namely by reviewing the contents of books, articles or journals, then continuing with the categorization of the results of the study which then ends with conclusions and research suggestions. The results show that the ethical concept of behaviorism is related to the moral theory proposed by Immanuel Kant, namely the concept of desired obligation and based on responsibility or autonomy. Then the aesthetic concept ofbehaviorism meets Immanuel Kant's aesthetic concept, namely subjective and objective aesthetics.